Trapping of plastics in semi-enclosed seas: Insights from the Bohai Sea, China. (December 2018) - Li, Yanfang; Wolanski, Eric; Dai, Zhenfei; Lambrechts, Jonathan; Tang, Cheng; Zhang, Hua
Abstract: Microplastics are abundant in semi-enclosed seas, presumably because of local trapping. To investigate this trapping effect, we confronted the SLIM plastic oceanography model with field data of the distribution of microplastics in the Bohai Sea, China. Seven source locations were selected to reveal the fate of plastic debris from industrial and domestic usages. The model predictions compared well with the observed distribution of microplastics, highlighting that most plastics were trapped in the Bohai Sea. The model suggests that microplastics distribution within the Bohai Sea both in the water and on the bottom varies seasonally with wind and currents and depends on a complex interaction between source locations, prevailing hydrodynamic conditions, degradation, settling and resuspension rates. Further field studies are warranted to enable the models to better parameterize the fate of microplastics, and particularly the accumulation zones, in other poorly flushed semi-enclosed seas worldwide, where microplastics should be classified as a persistent pollutant. Highlights: Seasonal variation of microplastic distribution was mainly controlled by currents and wind. Settling rate is a critical parameter determining the distribution of microplastic. The trapping process of microplastics in coastal sea is complex and important.